From Ideas to Implementations: Closing the Gaps between Technical Experts and Software Solutions - Smiley, Karen; Patel, Pankesh; Harding, Jeff (2016 IEEE/ACM International Workshop on Continuous Software Evolution and Delivery (CSED), 2016)
Rapid delivery strategies strive to balance critical performance qualities vs. reducing the time between an idea and deployment of a software implementation of that idea. For industrial software solutions that encapsulate expertise in deliverable components, technical SMEs (Subject Matter Experts) with ideas and knowledge have traditionally partnered as requirements providers with software development teams. These human processes are not optimally fast, are vulnerable to errors in translating or interpreting requirements, and do not scale when software teams need to integrate the knowledge of many SMEs into multiple software solutions and deployments. To address these limitations, ABB has pursued an industrial research initiative for innovative SME toolsets with focus on two goals: to accelerate the creation, evolution, reuse, and delivery of expert algorithms, and to streamline the deployment of these algorithms into releases and fielded solutions. The vision underpinning the initiative is to empower technical SMEs as "end-user developers" to convert their knowledge into reusable software solution components without having to learn, perform, or partner on traditional software development, integration, or deployment. In this paper, we summarize our experiences and lessons learned to date from this initiative, key continuing challenges, and some positional thoughts on how end-user development by technical SMEs aligns with emerging approaches for rapid delivery and evolution.